The endoplasmic reticulum stress status of CD4+ T lymphocytes and its association with mTOR-mediated autophagic-lysosomal disorder in elderly sepsis patients - Cheng, Wei; Zhang, Jiahui; Li, Dongkai; Xie, Yawen; Lei, Xianli; Wang, Hao; Cui, Na (Frontiers in Immunology, 2025)
Aimsto clarify the endoplasmic reticulum stress (ERS) status of CD4+ T lymphocytes in sepsis patients, particularly elderly individuals aged over 65 years, and to elucidate its association with mTOR-mediated autophagic-lysosomal disorder.Methods62 sepsis patients were enrolled from January 1 to July 31, 2024. Peripheral blood mononuclear cells (PBMCs) were isolated within 24 hours post-enrollment. flow cytometry was used to quantify the expression levels of ERS markers (CHOP and GRP78) and mTOR-mediated autophagic-lysosomal fusion markers (mTOR, LC3II and P62) on CD4+ T lymphocytes. These markers were compared between sepsis and non-sepsis patients, elderly and non-elderly sepsis patients, survivors and non-survivors based on in-hospital mortality. The correlations between CHOP mean fluorescence intensity (MFI) and CD4+ T lymphocyte count, LC3II MFI, and P62 MFI were also analyzed.ResultsCompared to non-septic controls, sepsis patients exhibited significantly higher CHOP and GRP78 MFIs (210.9 versus 142.9, P<0.001 and 279.1 versus 223.7, P=0.045). Within the sepsis group, elderly patients and non-survivors showed significantly higher CHOP and GRP78 MFIs (334.4 versus 164.2, P<0.001 and 374.3 versus 218.6, P<0.001; 390.8 versus 177.6, P<0.001 and 389.1 versus 227.0, P<0.001). CHOP MFI on CD4+ T lymphocytes showed significant correlations with LC3II and P62 MFIs in sepsis patients (Pearson’s correlation r=0.657, p<0.001 and r=0.811, P<0.001), elderly sepsis patients (r=0.644, P<0.001 and r=0.710, P<0.001), and non-survived elderly sepsis patients (r=0.897, P<0.001 and r=0.772, P=0.009).ConclusionERS in CD4+ T cells was enhanced in sepsis patients, particularly in elderly and non-survived individuals; ERS is strongly associated with mTOR-mediated autophagic-lysosomal disorder.Clinical trial registrationchictr.org.cn, identifier ChiCTR2300074175.